Structural and Ionic Conductivity Studies of CMC Based Polymer Electrolyte Doped with NH4Cl - Nur Hidayah Ahmad; Mohd Ikmar Nizam Mohamad Isa (Trasn Tech Publications, 2024)
The present study aims to investigate the structural and ionic conductivity of carboxymethyl cellulose - ammonium chloride as proton conducting polymer electrolytes. The complexion of polymer electrolyte films has been confirmed via FTIR studies. The conductivity enhancement with the addition of ammonium chloride concentration was proved due to the increase in amorphous nature of the films as evidenced XRD analysis. Impedance studies indicate that the highest ionic conductivity of 1.43 x 10-3 Scm-1 was observed with the addition of 16 wt.% ammonium chloride in polymer electrolyte system obtained at ambient temperature.